Determining the impact of biofilm in the bioaugmentation process of benzene-contaminated resources. Issue 1 (February 2021) - Naeimi, Maryam; Shavandi, Mahmoud; Alaie, Ebrahim
Abstract: Recently, petroleum contamination in groundwater has become one of the most common environmental problems. Bioaugmentation is proposed as a fully functional and economical technology by the addition of microorganisms to remove pollutants. The aim was to study the effect of biofilm formation of different species during the bioaugmentation of benzene removal in a Permeable Reactive Barrier (PRB) system based on calcium peroxide (CaO2 ) nanoparticles. Therefore, at first 3 strains identified with the ability to form biofilms and benzene degradation were isolated from groundwater. Subsequently, dissolved oxygen (DO), pH, the concentration of benzene, and microbial count of experimental columns were measured. Further, the examination of the biofilm formation on glass bead surfaces in bioaugmented and control reactors was also studied by confocal laser scanning microscopy (CLSM). The results of bioaugmentation show that adding Pseudomonas lini and Pseudarthrobacter polychromogenes can remove almost 80% of benzene from effluent after 70 days. Therefore, the study reveals the effect of bioaugmentation over intrinsic bioremediation. Also, the thicker and concentrated biofilm of Pseudomonas lini can be seen. This system provides a novel environmentally friendly technology for the in situ bioremediation of benzene. Graphical Abstract: ga1 Highlights: Petroleum contamination in groundwater has become one of the most common environmental problems. The effect of biofilm formation of different species during the bioaugmentation of benzene. Permeable Reactive Barrier (PRB). Using calcium peroxide (CaO2 ) nanoparticles.